Antibacterial Effect of Streptomyces sp-MWS1, Streptomyces sp-MWS3, and Streptomyces sp-MWS6 ON Klebsiella pneumoniae Producting Extended-Spectrum β-Lactamase (ESBL) - Setiawati, Yuani; Retnowati, Wiwin; Basori, Achmad (Jurnal Medis Islam Internasional, 2019)
Klebsiella pneumoniae as an opportunistic pathogen can cause nosocomial infection. The main concern on this bacterium is directed on the extended-spectrum β-Lactamase (ESBL)-producing Klebsiella pneumoniae. The therapy of ESBL-producing Klebsiella pneumoniae infections is very limited because of its multidrug resistance. It had been found new local isolates Streptomyces sp-MWS1, Streptomyces sp-MWS3, and Streptomyces sp-MWS6 in mangrove East Coast of Surabaya. These isolates have potential to produce antibiotics (Retnowati, 2008). This study was aimed to prove these isolates may inhibit the growth of ESBL-producing Klebsiella pneumonia. The test of antibacterial activity of Streptomyces sp-MWS1, Streptomyces sp-MWS3, and Streptomyces sp-MWS6 using the modification Agar print method against clinical isolates of ESBL-producing Klebsiella pneumoniae. The diameter of inhibition zone (mm) formed shows activity of these isolates. The profiles of antibacterial activity of Streptomyces sp-MWS1, Streptomyces sp-MWS3, and Streptomyces sp-MWS6 were different in terms of periode required to reach peak activity, duration of activity and inhibition zone diameter produced during 10 days of observation. Streptomyces sp-MWS3 reached the peak activity most rapidly on day 3 with the largest inhibition zone diameter of 9 mm in ESBL-producing Klebsiella pneumoniae. There were significant differences in inhibition zone diameter between Streptomyces sp-MWS1, Streptomyces sp-MWS3, and Streptomyces sp-MWS6 against ESBL-producing Klebsiella pneumoniae.